Latency and throughput analysis of a pipelined GDI ripple carry adder - Shylashree, N; S. Mahesh, D (International Journal of Engineering and Technology, 2018)
Latency and Throughput are deemed parameters of prime importance that determine the speed of an Adder Circuit. Ongoing research in the field of Digital Signal Processing involves optimizing an Adder regarding these parameters. This article picks up the study of a ripple carry adder and presents the use of two methods towards ameliorating the performance of an adder â€“ viz., the use of GDI (Gate Diffusion Input) technology for reduced Latency, and implementation of a pipelined architecture towards increasing the throughput. In this paper, we have dileneated the function of a basic GDI cell, with which a 1-bit ripple carry full adder was designed, which in turn formed the basic building blocks of 8-bit and 32-bit ripple carry adders. These full adders were designed using GDI technology while employing the concept of pipelining resulting in a novel structure optimizing both latency and throughput. This paper also presents a comparison among CMOS and GDI RCAs of 8 and 32bits with and without pipelining.On simulating 32-bit RCAs in Cadence virtuoso tool using gpdk 180nm technology ,those with pipelining had a 4.5 times increase in throughput with 42.8% increase in latency.Â